Error assessment of a three-dimensional underwater motion capture methodology - Thompson, I. M.; Audot, D. A. G.; Warner, M. B.; Banks, J.; Logan, O.; Hudson, D. (Sports Biomechanics, 2025)
Motion analysis technology is used in various settings to assess human kinematics. Assessing human movement underwater presents many challenges, making it important to understand measurement error associated with the setup and calibration of the system ensuring accuracy in resulting kinematics. This study assessed the accuracy across the entire domain of a submerged motion capture methodology. Six Qualisys cameras created an underwater capture volume of 6.9 × 2.1 × 2.1 m3. Average error levels were acceptable in four uncertainty trials (<± 5 mm error). By selecting an area of interest that excluded areas with low accuracy near domain borders, measurement error reduced by up to 0.13 mm, up to 1.27 mm lower than outside this area. Interpolated error indicated that intracyclic measurement error may alter measured kinematics by up to 13.80 mm, with error greater than 5 mm affecting over 50% of the kick cycle. Investigating error levels across the domain can inform researchers whether a recalibration is necessary or help to identify areas where high error levels would affect kinematics. This study highlights the need to investigate error levels across a motion capture domain, particularly when this is a large volume, to ensure results obtained from investigations are reliable.